Implementation of Minister of Home Affairs Regulation Number 13 of 2024 (Article 2) Concerning the Transition of Posyandu Duties and New Functions into Six Minimum Service Standard Sectors in Payakumbuh City - Syarah Nur Hakiki; Rahmadhona Fitri Helmi (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The transformation of Posyandu duties and functions into six Minimum Service Standard sectors requires local government readiness, cross-sector coordination, cadre capacity, budget support, and adequate facilities. This study aims to analyze the implementation of Minister of Home Affairs Regulation Number 13 of 2024 Article 2 concerning the transition of Posyandu duties and new functions into six Minimum Service Standard sectors in Payakumbuh City. A descriptive qualitative approach with a case study design was employed. Informants were selected through purposive sampling and included local government officials, urban village officials, and Posyandu cadres. Data were collected through in-depth interviews, observation, and documentation and were analyzed through data reduction, data display, and conclusion drawing based on the Van Meter and Van Horn policy implementation model. The findings indicate that the regulation has begun to be implemented but remains in a transitional stage. Several implementation constraints were identified, including the absence of detailed technical guidelines, limited competent human resources, unclear budget utilization, weak interorganizational coordination, varied community participation, and inadequate supporting facilities. This study concludes that the effective transition of Posyandu functions requires clearer operational standards, stronger institutional coordination, and improved resource readiness at the local level. The findings contribute to public policy implementation literature and provide practical implications for local governments in strengthening technical guidance, cadre training, budget planning, infrastructure provision, and cross-sector coordination.